EFEKTIVITAS SISTEM INFORMASI BERBASIS KOMPUTER - ARGO PAMUDI (Universitas Negeri Yogyakarta, 2005)
Abstract This research was aimed at finding out the effectiveness of the computer based information system in The Social Faculty of Yogyakarta State University (UNY). This study was a survey research. The result of this research is as follow: the computer based information system at the effectiveness of information system at the Faculty of Social Science of Yogyakarta State University has not optimal yet. Keywords: effectiveness, computer based information system